2005
DOI: 10.1016/j.eupc.2004.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Atrial pacing and sensing characteristics in heart failure patients undergoing cardiac resynchronization therapy

Abstract: Compared with patients with standard pacing indications, CRT recipients have less good electrical characteristics in the atrium. Atrial pacing and sensing function should be closely monitored in CRT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[7,8] In CRT, several studies have demonstrated the long-term electrophysiological stability and associated complications of conventional lead placement. [9-12] Alternate RV lead position in CRT has demonstrated similar hemodynamic effects as RV-A in previous studies. [13-16] However, there are few data concerning long-term electrophysiological stability and associated complications in alternate RV pacing sites in CRT.…”
Section: Introductionmentioning
confidence: 66%
“…[7,8] In CRT, several studies have demonstrated the long-term electrophysiological stability and associated complications of conventional lead placement. [9-12] Alternate RV lead position in CRT has demonstrated similar hemodynamic effects as RV-A in previous studies. [13-16] However, there are few data concerning long-term electrophysiological stability and associated complications in alternate RV pacing sites in CRT.…”
Section: Introductionmentioning
confidence: 66%
“…They comment that coexistent heart disease lowers impedance values. Another study by Schuchert et al (8) compared the atrial sensing and pacing parameters of CRT patients with dual chamber pacemaker patients. They found that pacing impedance did not differ between the groups at implantation but CRT patients showed significantly lower impedance values during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of AV synchrony to improving stroke volume in heart failure patients is well established [39,40]. In patients with severely reduced LV systolic function, any improvement in stroke volume from an appropriately timed atrial systole may be beneficial in improving hemodynamics [39,40].…”
Section: Does Av Dyssynchrony Affect Impella Hemodynamics?mentioning
confidence: 99%